2016
DOI: 10.1177/2050640615617636
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the Diverticular Inflammation and Complication Assessment (DICA) endoscopic classification on the outcome of diverticular disease of the colon: An international study

Abstract: DICA classification is a valid parameter to predict the risk of diverticulitis occurrence/recurrence in patients suffering from diverticular disease of the colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 34 publications
1
28
0
3
Order By: Relevance
“…It subdivides patients as having three increasing score of severity: DICA 1, DICA 2, and DICA 3 (9). We found that this classification was able to predict the outcome of the disease according to DICA score severity in term of acute diverticulitis occurrence/recurrence and in term of surgery occurrence (10). Moreover, the same study found that only DICA 2 patients might benefit from a scheduled therapy during the follow-up in term of acute diverticulitis occurrence/recurrence and in term of surgery occurrence (10).…”
Section: Methodsmentioning
confidence: 90%
See 4 more Smart Citations
“…It subdivides patients as having three increasing score of severity: DICA 1, DICA 2, and DICA 3 (9). We found that this classification was able to predict the outcome of the disease according to DICA score severity in term of acute diverticulitis occurrence/recurrence and in term of surgery occurrence (10). Moreover, the same study found that only DICA 2 patients might benefit from a scheduled therapy during the follow-up in term of acute diverticulitis occurrence/recurrence and in term of surgery occurrence (10).…”
Section: Methodsmentioning
confidence: 90%
“…Moreover, elective operations for diverticulitis rose up to 29% in the same period, especially in younger people (73% in rates of surgery for those individuals) (19). We have recently found DICA endoscopic classification as predictor of the outcome of DD in term of prevention of acute diverticulitis occurrence/recurrence and in term of surgery occurrence prevention: DICA 1 patients were always at very low risk of complications, and DICA 3 patients were always at very high risk of complications, despite scheduled therapy (10). Scheduled treatments in order to prevent acute diverticulitis occurrence/recurrence and surgery occurrence seem to be appropriated only in DICA 2 patients, and the mesalazinebased and the association mesalazine/rifaximin are the only treatments significantly effective (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations